CAMPATH-IH in multiple sclerosis. - Moreau, T; Coles, A; Wing, M; Thorpe, J; Miller, D; Moseley, I; Issacs, J; Hale, G; Clayton, D; Scolding, N; Waldmann, H; Compston, A (1996)
In a pilot study, seven patients with multiple sclerosis were treated with CAMPATH-IH which targets the CD52 antigen present on lymphocytes and monocytes. There was a substantial reduction in disease activity as measured by gadoliunium-enhancing lesions on MRI. Encouraged by this result a further seven patients have been treated with CAMPATH-IH; four also received anti-CD4 antibody. Lymphopaenia developed rapidly and was sustained for at least one year. In 12 patients, the first infusion of antibody was characterised by significant exacerbation or re-awakening of pre-existing symptoms lasting several hours. These clinical effects of antibody treatment correlated with increased levels of circulating cytokines. Peak levels of tumour necrosis factor alpha (TNF alpha) and interferon gamma (IFN gamma) occurred at 2 h whereas the rise in interleukin-6 (IL-6) was significantly delayed and peaked at 4 h after starting antibody treatment. The neurological symptoms could not be attributed directly to pyrexia and were not provoked (in one patient) by an artificial rise in temperature. In the remaining two patients, a single pre-treatment with intravenous methylprednisolone (500 mg) prevented both the transient increase in neurological symptoms and the cytokine release. Our results suggest that soluble immune mediators contribute to symptom production in multiple sclerosis by directly or indirectly blocking conduction through partially demyelinated pathways.